Islam in the modern society of Kazakhstan (Journal of Philosophy Culture and Political Science, 2018)
This work is devoted to the theological analysis of influence of a religious factor, in particular, Islam on further modernization of the Kazakhstan society. Key words: Religion, Islam, faith, dialogue, tengrianstvo, zoroastrism, shamanizm, national state, sovereignty, focused on the Muslim state, modernization.